Com quantos seguidores se faz um food truck? : a influência do Instagram na comunicação dos food trucks aracajuanos - Costa, Yuri Nascimento (2019)
The beginning of the 21st century witnessed a phenomenon triggered by technological advances and the massification of networked communication. This new context profoundly changed social practices, especially the consumption relationship between individuals and organizations. Already the food habit is one of the most traditional cultural factors of life in society, however, the advent of digital social media allowed one of the oldest commercial segments, street food, could be reformulated from new concepts of consumption and communication. The food truck, a business model that came to Brazil in early 2012, had its origins in the United States, a country that created and developed the format over the last two centuries and linked food consumption to communication through social networks. This trend reached Aracaju, the capital of Sergipe, at the end of 2014, which also started using digital platforms to dialogue with its consumers. In view of this contemporary phenomenon, the present study decided to analyze the role of Instagram as a communication tool between Aracaju/SE food trucks and their consumers. The research, which had three phases, began its investigation with a survey of scientific references on the subject and a documentary immersion that made possible the construction of the theoretical reference. In the methodological perspective, a qualitative exploratory approach was adopted, using as instruments for data collection the direct observation of the segment in the physical and virtual environment, and semi-structured interviews with the owners of three food trucks of Aracaju. During the investigation, it was necessary to triangulate methods between the quantitative and qualitative approach, aiming at the full interpretation of the information collected (DENZIN and LINCOLN, 2006). Then, a content analysis was carried out, based on Bardin (2016), regarding the publications published in the Instagram of the three food trucks of Aracaju between July 18, 2017 and July 18, 2018. Finally, it was structured, with Jensen and Jankowski (1993), a triangulation of the data and information collected at each stage of the research. This triangulation allowed the understanding of the work regarding the fundamental importance that the Instagram exerts in the communication between the food trucks of Aracaju and their clients. In addition, it was possible to map the profile of entrepreneurs in this segment and to record all food trucks that operated between 2017 and 2018 in the Sergipe capital. Finally, it was concluded, through digital content, that food trucks have been carrying out communication strategies without due strategic planning. This entails actions inconsistent with the company's communication concept, as well as preventing a diversification capable of making the social bond of the public with institutions more efficient. Nevertheless, the characteristics of Instagram allowed the communication practiced to trigger significant interactions between food trucks and their consumers.